Life satisfaction of Paralympians: The role of needs satisfaction and passion - Rodrigues, Filipe (2022)
The current study examined the possible role of basic psychological needs and passion in Paralympians’ life satisfaction. A mediational model was tested where autonomy, competence and relatedness were hypothesized to be linked to athlete life satisfaction via harmonious and obsessive passion. The sample comprised 91 Portuguese Paralympians aged between 18 and 59 years (M = 31.01; SD = 3.78). Athletes completed self-reports of needs satisfaction in their sport, passion towards their sport, and general life satisfaction. Perceptions of competence and relatedness were associated with harmonious passion (β = .37, p > .01; β = .21, p > .05, respectively), while perceptions of autonomy were associated with obsessive passion (β = .39, p > .05). Additionally, harmonious passion, but not obsessive passion, was associated with life satisfaction (β = .40, p > .01), and only the indirect effect from competence to life satisfaction, via harmonious passion, was significant. These results suggest that feeling autonomous may not necessarily translate into more harmonious passionate engagement but is associated with higher levels of obsessive passion. In contrast, competence and relatedness appear to play an important role in the life of athletes who experience a more harmonious passion towards their sport practice. Perceptions of mastery and competence, as well as sport-related social connections could be important to consider improving the lives of athletes with Paralympic experience.